(untitled) (Transport systems and technologies, 2020)
Important characteristic of magnetic-field with the high measure of intensity and heterogeneity in the swept volume of the electromagnetic systems is a size of tension of the field Н. Calculation of tension in the field H in these systems, characterized by relatively large air interval, given its three-dimensionalty, presents a very difficult task. Analytical decision of equalization of Laplace that describes distribution of magnetic-field in the interpolar volume of the axisymmetrical magnetic systems, difficultly from difficult geometry of bodies that is included in a calculation area, that is why for research of distribution of tension the expedient use of numeral methods of calculation - to the method of eventual differences, method of eventual elements, method of maximum integral equalizations. The calculation of distribution of scalar magnetic potential in open magnetic systems with the use of numeral methods of calculation causes the difficulties related to limitation of calculation area in which the calculation is conducted. The static magnetic fields, analysed in this research, obey one of basic equalizations of mathematical physics, and namely, to equalization of Laplace in partial differential. In case of calculation of magnetic field of the axisymmetrical magnetic systems it is necessary to resolve the Cauchy problem for equalization of Laplace. It is known, that this task does not have characteristic of steadyness, and thus does not obey Hadamars third condition of correctness and, therefore, is considered incorrectly defined. For the number of unsteady tasks of mathematical physics of R.Lattes and ZH.Lions developed the quasi-random method, that can be applied both for evolutional tasks, as well as for constant. The basic idea of quasi-random method lays in proper update of differential operators that are part of the task. This change is done by introducing additional differential elements. Application of this method allows to use effectively the numeral methods of calculation of regional task for open axisymmetrical systems.